Construction of indigenous plant extract library for anti-cancer activity - Jamil, Noor Izani Noor (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2010)
Barringtonia racemosa, Syzygium polyanthum, Oroxylum indicum and Vitex pinnata are edible plants commonly consumed as salads and also used in traditional herbal medicine. These plants were believed to possess anticancer, anti-inflammatory and anti-diabetic properties, among others. Thus, we seek to determine the antiproliferative and apoptosis activity of the methanol leaves extracts of these plants on the growth of cervical cancer cell line, HeLa using methyl1;1ne blue assay. The methanol leave extract of 0. indicum exerted the strongest antiproliferative activity towards HeLa cells with IC5o 3.87 jlg/ml without affecting non-malignant cell lines tested (V ero, MOCK, L929) compared to Cisplatin IC50 of I 0.09 jlg/ml to He La cells. Barringtonia racemosa, Syzygium polyanthum, and Vitex pinnata showed an IC5o of 8.52, 34.06 and 9.69 jlg/ml on HeLa cells respectively. However, Barringtonia racemosa and Syzygium polyanthum showed cytotoxic effect on the non-malignant cell lines. Thus, 0. indicum was selected for nuclear staining by means of Hoechst staining to access apoptosis events. DNA fragmentation was seen in treated cells and apoptotic bodies occurred during 24, 48 and 72 hours treatment as was seen in Cisplatin treatment (positive control drug). Phytochemical screening of 0. indicum methanol leaves extract indicated the presence of flavonoids, tannins, triterpenes and steroids which may be responsible for the anti-proliferative and apoptosis activities towards HeLa cells. The findings suggested that 0. indicum has the selective antiproliferative activity on HeLa cells by inducing apoptosis.